Implementasi Kurikulum Berbasis IT dalam Sekolah dimasa Pandemi Covid-19 - Sugiati Sugiati (Departement of Mathematics Education, 2021)
This study aims to implement the curriculum by utilizing information and communication technology during the pandemic which in the process is distance learning. Teachers without face-to-face with students are expected to continue to maximize the learning process and maintain the quality of graduates by utilizing technology. The curriculum which is used as the spirit of education in schools is expected to be a reference for future learning progress. Whether or not the process is progressing or not, the success or failure of the process all depends on the curriculum developed by the school. This implementation must involve all stakeholders by preparing the readiness of the infrastructure and human resources owned by the infrastructure readiness teachers, at least the government procures funds for infrastructure facilities such as computers, internet connections, while for the readiness of teacher human resources, schools hold training on the use of MO365 from the Surabaya City Education Office and Google account suite. learn ID from the Ministry of Education and Culture. The implementation includes, the preparation of 1 curriculum documents using the D-One application, the preparation of lesson plans without printing or paperless, for file storage also using Google Drive or One Drive, preparing questions using office forms, vicon learning using Zoom Meet, Teams Meet, and Google. meet, entry of grades using an online report card application, besides that the school also has a website, Instagram, YouTube for publication of school activities. The school minimizes if there are obstacles related to the implementation of the IT-based curriculum by completing multimedia facilities and providing training to teachers in IT skills. The results of the implementation of the IT-based curriculum show that the achievement of the curriculum targets is above 80% as evidenced by the learning outcomes of students, as well as responses from school activities that have been published through the school's website, Instagram and YouTube.